2012
DOI: 10.1242/jcs.107318
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive lysosome exocytosis releases ATP and engages P2Y receptors in human monocytes

Abstract: SummaryElucidating mechanisms by which Ca 2+ signals are generated by monocytes is important for understanding monocyte function in health and disease. We have investigated mechanisms underlying Ca 2+ signals generated following disruption of lysosomes by exposure to the cathepsin C substrate glycyl-L-phenylalanine-b-napthylamide (GPN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…In addition, previous studies have demonstrated that Dictyostelium can condition growth medium with ATP (10). This suggests that Dictyostelium amoebas secrete ATP constitutively, as do some mammalian cells (15,18). Our own bulk phase measurements suggest a relatively high basal level of extracellular ATP, between 2 and 4 M. In this study, inhibition of vesicular secretion with NEM or by drainin knockout did not affect the level of basal ATP, though NEM strongly inhibited ATP release during swelling.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…In addition, previous studies have demonstrated that Dictyostelium can condition growth medium with ATP (10). This suggests that Dictyostelium amoebas secrete ATP constitutively, as do some mammalian cells (15,18). Our own bulk phase measurements suggest a relatively high basal level of extracellular ATP, between 2 and 4 M. In this study, inhibition of vesicular secretion with NEM or by drainin knockout did not affect the level of basal ATP, though NEM strongly inhibited ATP release during swelling.…”
Section: Discussionmentioning
confidence: 40%
“…Furthermore, vesicular ATP release is one of numerous mechanisms proposed as modes of ATP secretion in mammalian cells (18). Therefore, we sought to employ N-ethylmaleimide (NEM), which blocks vesicular exocytosis and ATP release in mammalian cells (15). NEM caused profound swelling and loss of regulatory cell volume decrease under hypotonic conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…How A␤1-42 induces ATP release from glial cells is largely unknown. Lysosomal exocytosis of ATP has been reported for several types of glial cells or monocytes induced under various conditions (11,35,(49)(50)(51). Whether the A␤1-42-induced ATP release in glial cells is also through lysosomal exocytosis needs further clarification.…”
Section: Discussionmentioning
confidence: 97%